(untitled) (Indonesian Journal of Agrarian Law, 2026)
Legal protection for landholders still faces challenges in practice when national infrastructure projects physically alter land conditions without adequate follow-up mechanisms. This article examines the legal protection afforded to holders of land rights in Grogolan Village, whose land has been affected by the construction of the Pengapon–Boyolali (BBM) oil pipeline transmission project carried out by PT Pertamina Patra Niaga. This study employs an empirical legal approach, combining field observations, in-depth interviews with affected landowners, village officials, and the Boyolali District Land Office (BPN), supplemented by an analysis of relevant legislation. The research findings indicate that legal protection for land rights holders in Grogolan Village has not yet been substantively realised. Applying Satjipto Rahardjo’s theory of legal certainty as the theoretical basis for evaluating legal protection, deficits were identified in all four of its constituent elements, physical changes to the land were not officially recorded in land documents, land certificates did not reflect the actual post-construction conditions, buffer zone restrictions were never formally communicated to landowners, and there was no active notification mechanism from Pertamina to the BPN. A public consultation that was not inclusive involving only two representatives from around 40–50 affected farmers demonstrates a failure to fully comply with Law No. 2 of 2012 on Land Acquisition for Public Interest. It is recommended that the regulations be amended to require energy infrastructure project implementers to facilitate the certificate splitting process and provide comprehensive the rights, obligations, and land use restrictions arising from pipeline corridors.